2013
DOI: 10.5539/ijbm.v8n12p29
|View full text |Cite
|
Sign up to set email alerts
|

Student Acceptance of Knowledge Management Systems: Evidence from a Canadian Business School

Abstract: This study investigates the factors affecting the perceived usefulness of and the intention to use knowledge management (KM) systems by students. The research model posits that the intention to use KM systems in higher education depends on perceived usefulness, perceived user-friendliness, organizational rewards, and community of practice. A survey method was used to collect the data for the study. We used a convenience sample consisting of undergraduate students enrolled in various business courses in a Canad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
(55 reference statements)
0
0
0
Order By: Relevance
“…When academic staff perceives that using web technology for KS requires little effort, they will be more likely to share their knowledge with others (Fan & Wu, 2011). In previous literature, Hossain et al (2013), Tsai (2014), as well as Fan & Wu (2011) emphasize the significance of the perceived ease of use of technology for KS. Hossain et al (2013)showed that perceived ease of use significantly predicts an intention to use knowledge management systems.…”
Section: Perceived Ease Of Usementioning
confidence: 99%
See 2 more Smart Citations
“…When academic staff perceives that using web technology for KS requires little effort, they will be more likely to share their knowledge with others (Fan & Wu, 2011). In previous literature, Hossain et al (2013), Tsai (2014), as well as Fan & Wu (2011) emphasize the significance of the perceived ease of use of technology for KS. Hossain et al (2013)showed that perceived ease of use significantly predicts an intention to use knowledge management systems.…”
Section: Perceived Ease Of Usementioning
confidence: 99%
“…When academic staff considers using web technology might enhance their job performance, they are more likely to be encouraged to share their knowledge via the system (Tsai, 2014). According to Hossain et al (2013), perceived usefulness is one of the predictors of intention to use knowledge management systems. Tsai (2014) and Fan & Wu (2011) also found that perceived usefulness significantly affected usage intention.…”
Section: Perceived Usefulnessmentioning
confidence: 99%
See 1 more Smart Citation